2018
DOI: 10.1007/s10616-017-0179-z
|View full text |Cite
|
Sign up to set email alerts
|

Primary culture of lung fibroblasts from hyperoxia-exposed rats and a proliferative characteristics study

Abstract: Lung fibrosis is an ultimate consequence of bronchopulmonary dysplasia (BPD) which shows the excessive proliferation of lung fibroblasts (LFs). To find a better model for studying the role of LFs in hyperoxia-induced lung fibrosis at the cellular level, we isolated LFs from the lung tissue of hyperoxia- and normoxia-exposed rat lungs on postnatal days 7, 14 and 21 for primary culture to study their proliferative behavior. In the present study, the LF predominance was > 95% in our culture method. The LFs isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(30 reference statements)
1
4
0
Order By: Relevance
“…Our previous study found that LFs isolated from rats exposed to hyperoxia in vivo showed significantly greater proliferation compared with those from rats exposed to normoxia. In addition, using flow cytometry, it was revealed that the percentage of LFs in the S and G 2 /M phases increased, and the proportion of LFs in the G 0 /G 1 phase decreased simultaneously (10). In another study, we confirmed that 5-aza-2'-deoxycytidine, a DNA methylation inhibitor, inhibited hyperoxia-induced LF proliferation by restoring p16 expression (11).…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Our previous study found that LFs isolated from rats exposed to hyperoxia in vivo showed significantly greater proliferation compared with those from rats exposed to normoxia. In addition, using flow cytometry, it was revealed that the percentage of LFs in the S and G 2 /M phases increased, and the proportion of LFs in the G 0 /G 1 phase decreased simultaneously (10). In another study, we confirmed that 5-aza-2'-deoxycytidine, a DNA methylation inhibitor, inhibited hyperoxia-induced LF proliferation by restoring p16 expression (11).…”
Section: Introductionsupporting
confidence: 51%
“…Excessive LF proliferation is a key process in pulmonary fibrosis, and abnormal regulation of the cell cycle at the G 1 /S phase is necessary for hyperoxia-induced LF overproliferation (10). Our previous study found that exposure to hyperoxia weakened the G 1 /S checkpoint, enabling more LFs to pass this checkpoint and progress from the G 1 phase to the S and G 2 /M phases to complete DNA replication; this phenomenon promotes eventual LF division and proliferation (10).…”
Section: Discussionmentioning
confidence: 99%
“…This results in tissue remodeling, developmental disorders, and interstitial fibrosis that may ultimately lead to the development of BPD [ 14 , 15 ]. This pathology is clearly observed in the immature lung cells of newborn rats that develop BPD [ 16 ]. Using hematoxylin–eosin staining and immunohistochemistry methods, we have found that the immature lungs exposed to long-term hyperoxia result in fibrogenesis and a significantly higher expression of p-ERK protein in both lung tissue and primary cultured fibroblasts of newborn Wistar rats [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lungs were isolated from neonatal Sprague–Dawley rats to prepare PFs using the differential adherent properties of fibroblasts as previously described with minor modifications [ 19 ]. Briefly, neonatal rats were euthanized by CO 2 asphyxiation and the lungs were excised under sterile conditions.…”
Section: Methodsmentioning
confidence: 99%